Primary cutaneous diffuse large B-cell lymphoma, leg type – case report - Przekazińska, Katarzyna; Stankiewicz, Urszula; Brzezicka-Ciach, Urszula (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . Primary cutaneous lymphomas are a heterogeneous group of malignant tumours, which at the time of diagnosis involve only the skin. Sixty-five percent of them refer to T-cells, 25% to B-cells and NK cells or other rare forms comprise about 10%. Primary cutaneous B-cell lymphomas are less common, and they are considered less important than the group of T-cell lymphomas. Objective . To present a patient with a rare case of primary cutaneous B-cell lymphoma. Case report . A 72-year-old woman was admitted to the Department of Dermatology due to skin lesions on both lower legs consisting of bluish-red nodules, hard and cohesive in palpation. Laboratory tests did not reveal any abnormalities. In skin biopsy from a nodular lesion primary cutaneous B-cell lymphoma, leg type was diagnosed. The patient was referred to the Department of Chemotherapy, where the staging of the disease according to the Ann Arbor scale was made and a regimen of R-CHOP chemotherapy (6 courses) was applied. Post-treatment PET (positron emission tomography) examination did not show any abnormalities. Conclusions . Primary cutaneous B-cell lymphoma, leg type is a rare malignancy comprising approximately 2-5% of all primary cutaneous lymphomas. The pathogenesis is unclear. Clinically it may mimic erythema induratum or vasculitis nodosa, which occur quite often. Due to the rapid progression of the disease and high metastasis rate it is important to make a quick diagnosis and treatment.